2017
DOI: 10.1126/science.aal3422
|View full text |Cite
|
Sign up to set email alerts
|

Imaging the distribution of transient viscosity after the 2016 M w 7.1 Kumamoto earthquake

Abstract: The deformation of mantle and crustal rocks in response to stress plays a crucial role in the distribution of seismic and volcanic hazards, controlling tectonic processes ranging from continental drift to earthquake triggering. However, the spatial variation of these dynamic properties is poorly understood as they are difficult to measure. We exploited the large stress perturbation incurred by the 2016 earthquake sequence in Kumamoto, Japan, to directly image localized and distributed deformation. The earthqua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
69
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 80 publications
(76 citation statements)
references
References 41 publications
6
69
1
Order By: Relevance
“…These aftershocks may be attributed to the brittle creeping fault zone mechanism, because the depth is consistent with the brittle and ductile transition (Perfettini & Avouac, ). Areas at the southwestern end of the main fault plane (segment 3, Figure b) present limited postseismic deformation or after slips (Moore et al, ), and the microseismicity are widely distributed from 5 km to 18 km, which indicates that the coseismic stress triggering (first mechanism) may be the dominant triggering mechanism. Two areas with substantial Coulomb stress increase present limited aftershocks, that is, the shallow slip deficit area and the downdip edge of the last asperity (Seg 1 in Figure b).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…These aftershocks may be attributed to the brittle creeping fault zone mechanism, because the depth is consistent with the brittle and ductile transition (Perfettini & Avouac, ). Areas at the southwestern end of the main fault plane (segment 3, Figure b) present limited postseismic deformation or after slips (Moore et al, ), and the microseismicity are widely distributed from 5 km to 18 km, which indicates that the coseismic stress triggering (first mechanism) may be the dominant triggering mechanism. Two areas with substantial Coulomb stress increase present limited aftershocks, that is, the shallow slip deficit area and the downdip edge of the last asperity (Seg 1 in Figure b).…”
Section: Resultsmentioning
confidence: 99%
“…We processed a SAR interferogram over 6 months after the mainshock showing postseismic ground deformation near the source area (Figure ). This was also revealed by SAR time series analysis (Moore et al, ). The postseismic deformation field presents localized deformation in comparison with the coseismic deformation field (Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent tomographic studies show that the 2016 Kumamoto earthquake occurred in a strong patch (with a low attenuation and a high velocity) in the upper crust but was underlain by arc magma and fluids in the lower crust and upper mantle wedge (with a high attenuation and a low velocity; H. Wang et al, ; Z. W. Wang et al, ; Zhao et al, ). Many studies have demonstrated that fluids and arc magma exist under the Aso active volcano near the Kumamoto source zone: for example, a high‐temperature (over ~500 °C) anomaly at ~3‐km depth beneath the Aso caldera (Okubo & Shibuya, ), a prominent low‐velocity anomaly indicating a magma chamber (H. Wang et al, ; Xia et al, ; Yu et al, ; Zhao et al, ), a broad low‐viscosity anomaly in the lower crust (Moore et al, ), a large velocity reduction caused by pressurized volcanic fluids (Nimiya et al, ), and volcanic rocks containing components of slab‐derived fluids (Kita et al, ). Coulomb stress changes indicate that the high‐temperature and widespread fluids around the Aso volcano also stopped the rupture of the Kumamoto mainshock (Yue et al, ; Zhang et al, ).…”
Section: Discussionmentioning
confidence: 99%